Fintech Solusi Mengatasi Kesenjangan Akses Keuangan di Indonesia - Nasution, Riandi Pathan; Alif, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Indonesia, a country with abundant natural resources and a dynamic population, possesses great economic potential yet faces welfare leveling challenges, particularly access to financial services. Rural and vulnerable communities still have difficulty accessing formal financial institutions, impacting significantly on poverty, education, and economic opportunity. Advances in digital technologies, particularly Financial Technology (Fintech), offer innovative solutions to address these issues. This qualitative research, using the literature study method, analyzes the role of Fintech in addressing the financial access gap in Indonesia. The literature review includes scientific journals, official reports, and related regulatory documents. Fintech is proven to provide faster, more efficient, and more accessible access to financial services. However, the study also identified challenges faced, such as data security risks, incomprehensive regulation, low digital literacy, uneven technology infrastructure, potential for fraud, shortage of skilled human resources, and suboptimal integration with conventional financial systems. Therefore, the collaboration of government, industry, and society is required to maximize the potential of Fintech and minimize its risks, in order to achieve the leveling of economic well-being in Indonesia.